Vessel wall MRI in ruptured cranial dural arteriovenous fistulas. Issue 4 (August 2021) - Cord, Branden J; Renedo, Daniela; Santarosa, Corrado; Sujijantarat, Nanthiya; Antonios, Joseph; Kim, Jennifer A; Falcone, Guido J; Sheth, Kevin N; Malhotra, Ajay; Matouk, Charles C
Intracranial high-resolution vessel wall MRI (VW-MRI) is an imaging paradigm that is useful in site-of-rupture identification in patients presenting with spontaneous subarachnoid hemorrhage and multiple intracranial aneurysms. Only a handful of case reports describe its potential utility in the evaluation of more complex brain vascular malformations. We report for the first time three patients with ruptured cranial dural arteriovenous fistulas (dAVFs) that were evaluated with high-resolution VW-MRI. The presumed site-of-rupture was identified based on contiguity of a venous ectasia with adjacent blood products and thick, concentric wall enhancement. This preliminary experience suggests a role for high-resolution VW-MRI in the evaluation of ruptured cranial dAVFs, in particular, site-of-rupture identification. It also supports an emerging hypothesis that all spontaneously ruptured, macrovascular lesions demonstrate avid vessel wall enhancement.